The Value of Helping in "Tingkeban" in Coblong District, Bandung City, West Java - Wiwit Subandiyah; Babang Robandi; Dian Penisiani (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
The purpose of writing this paper is to describe and explain the educational values ​​contained in the tingkeban tradition in Coblong District, Bandung City. Method used in writing this paper is a qualitative method using literature review techniques. The scope of this paper includes the meaning, origins, process of tingkeban and the educational values ​​contained in this activity. The purpose of writing this paper is to introduce and provide an overview of the tingkeban tradition which contains educational values ​​such as the value of mutual help which teaches the attitude of helping each other in lightening the burden which can be used as a basis for developing children's character at school.